FREE ECONOMIC ZONES IN UZBEKISTAN: REGIONAL DEVELOPMENT AND EXPORT OPPORTUNITIES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Today, free economic zones are playing an important role in developing the economy, attracting investments and creating new jobs. They serve as an effective platform for modernizing industrial sectors, producing competitive products and expanding export potential. Therefore, free economic zones are considered an important tool for the sustainable development of the country's economy. Their activities serve to strengthen regional economic activity and accelerate integration with the international market.